Improvement of the Mechanical Characteristics, Hydrogen Crack Resistance and Durability of Turbine Rotor Steels Welded Joints - Alexander I. Balitskii; Vitaly V. Dmytryk; Lyubomir M. Ivaskevich; Olexiy A. Balitskii; Alyona V. Glushko; Lev B. Medovar; Karol F. Abramek; Ganna P. Stovpchenko; Jacek J. Eliasz; Marcin A. Krolikowski (Energies, 2022)
This article is devoted to the following issues: calculating the values of temperatures obtained by simulating welding heating and the subsequent implementation of the welding process at the given mode parameters made it possible to obtain a welded joint of the rotor with an improved initial structure and increased mechanical properties, hydrogen resistance and durability by up to 10–15%; simulating welding heating in the areas of fusion, the overheating and normalization of the HAZ and the formation of austenite grains; specified welding heating creates the conditions for the formation of new products of austenite decomposition in the form of sorbitol in the area of the incomplete recrystallization of the HAZ. In air and gaseous hydrogen, the destruction of the combined joints took place on the weld metal, as well as on the fusion areas, the overheating and the incomplete recrystallization of the HAZ of 20H3NMFA steel as the base metal. Structural materials have a relatively low strength and high fracture toughness in air. This is manifested in a significant reduction in the elongation (δ), the area (ψ) and critical stress intensity factor (KIc) of welded joints and the endurance limit of cylindrical smooth rotor steel specimens, which were cut from transverse templates. Welded joints in the whole range of load amplitudes are sensitive to the action of hydrogen.